2016
DOI: 10.1007/s11356-016-6968-7
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium (Cd) distribution and contamination in Chinese paddy soils on national scale

Abstract: Rice is a staple food by an increasing number of people in China. As more issues have arisen in China due to rice contaminated by cadmium (Cd), Cd contamination in arable soils has become a severe problem. In China, many studies have examined Cd contamination in arable soils on a national scale, but little studies have focused on the distribution of Cd in paddy fields. This study explored the spatial pattern of Cd in paddy soils in China, made a preliminary evaluation of the potential risk, and identified the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(50 citation statements)
references
References 23 publications
(31 reference statements)
1
41
0
Order By: Relevance
“…Anthropogenic activities and mining are major sources of metals accumulation in soils, especially in agricultural soils [1,2]. The pollution of Cd in paddy soils is a widespread problem due to its potential harm to plants and human health [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropogenic activities and mining are major sources of metals accumulation in soils, especially in agricultural soils [1,2]. The pollution of Cd in paddy soils is a widespread problem due to its potential harm to plants and human health [3].…”
Section: Introductionmentioning
confidence: 99%
“…The pollution of Cd in paddy soils is a widespread problem due to its potential harm to plants and human health [3]. Rice (Oryza sativa L.) is a widely cultivated crop in China [1], and also a common dietary source for Cd and As exposure. A number of studies have reported that metal contents exceed safe values [4].…”
Section: Introductionmentioning
confidence: 99%
“…Biotechnology Research Institute, Chinese Academy of Agricultural Sciences, Beijing, China. 2 College of Life Science and Technology, Jinan University, Guangzhou, Guangdong, China.…”
Section: Construction Of Plasmids For Gene Fragments Heterologous Expmentioning
confidence: 99%
“…Soil contamination with heavy metals is becoming an increasingly urgent problem worldwide. Among all heavy metals, one of the most hazardous is cadmium (Cd) [1,2]. Cd is a non-essential heavy metal element that is toxic, teratogenic and carcinogenic to humans.…”
Section: Introductionmentioning
confidence: 99%
“…Rice is a staple food for nearly 60% of China's population and has very important planting status in China. However, in recent years, it is not uncommon to find the reports that the cadmium content of rice has exceeded the standard due to soil pollution (Liu et al 2016a). This study is from the perspective of practical production and application.…”
Section: Introductionmentioning
confidence: 99%